Comparing cost implications of renewable energy and grid energy use in the South African mining sector - Smit, Adriaan J (My University, 2021)
Mining is a significant benefactor to the African continent's economy as mineral exports contribute significantly to the Gross Domestic Product of many countries. While mining is playing a positive developmental role, it is faced with numerous challenges that constrain its performance. Among these are industrial and infrastructure challenges, such as electricity constraints that have proven to be a significant problem facing the mining industry on the continent. South Africa’s development exceeds that of most other African countries but has also been experiencing electricity challenges resulting from infrastructure constraints and the inability of the power system to meet current demands. Looking at the potential of renewable forms of energy (REN) within South Africa, a potential opportunity exists that can contribute towards addressing electricity challenges, and this needs to be explored, especially in the mining industry. This will enable the mining operations to increase the production and beneficiation of minerals without solely depending on a centralised electricity system to provide power. Electricity is critical for running a mining operation. Relevant surface infrastructure, processing plants, and neighbouring communities also require electricity to support the mining operation and the mining value chain's activities. Mineral extraction and full-scale mining activities in South Africa have fallen short with the erratic and unpredictable supply from Eskom with multiple bouts of, often extended periods of load shedding. South Africa’s 2019’s mining GDP came in at R 226 billion, significantly less than the preceding year (R 351 billion) as a direct consequence of load shedding (Minerals Council of South Africa, 2019). The energy challenges experienced by South Africa has necessitated the mining industry to look at alternative sources of energy in order to move away from relying solely on electricity supplied by Eskom to ensure feasible and sustainable operations. The objective of the study was to investigate the feasibility of alternative sources of energy by comparing the cost implications of renewable energy and grid energy use in the mining industry. Using quantitative research, this study looked at the capital and operational expenditure of powering a medium to large scale operation on multiple scenarios of REN. Numerous financial models and scenarios were tested to conclude on an independent, feasibly sustainable and practical solution for power supply other than grid-supplied energy from a centralised distributor. REN proved to be attractive compared to grid-tied energy and offered several solutions depending on the practicality applicable to the relevant operation. The results show that REN options that are currently on the market can power 70ktpm underground operation. Hydropower had the best return (IRR) and project value (NPV) followed by the solar-only option giving no consideration to back-up power or storage to be utilised after sunset. However, both of these options were found to have practical challenges. Hydropower can only be considered where a consistent flow of a sufficient water mass exists year-round, and the solar-only option can only function during the daytime. To combat this, the analysis looked at alternative scenarios to supply energy during cyclic changes associated with daily or seasonal variations in nature. Lithium-ion batteries (LIB) stood out as an appropriate consideration for the storage of power but proved to be expensive in their current making the solar with battery storage unfeasible. Based on the results obtained, it is concluded that an opportunity for REN exists and that REN can be feasibly implemented. The installation of REN can reduce and/or eliminate the reliance on a grid-tied source of electricity. However, the cost of storage to ensure stable and undisturbed supply remains a barrier. While the focus of the report was to find a solution away from the grid-tied electricity, under current conditions the feasible option may include considering a hybrid set-up where a mining operation is connected to grid power and supplemented by solar for as long as the daylight allows. This will eliminate the need for expensive power storage and has the potential to realise power cost savings. As mentioned, some mining companies like Sibanye Stillwater are considering this option. Given the REN landscape in South Africa, clear policy and legislation guidelines are important to encourage investments in REN and as such mining companies should engage with the relevant regulators and government departments to scope out a denser REN future. There is potential for cost savings and for the SA mining industry to become a significant role-player in the REN setup
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Engineering, 2021